Prior cytopenia predicts worse clinical outcome in acute myeloid leukemia. Issue 10 (October 2015) - Huck, Amelia; Pozdnyakova, Olga; Brunner, Andrew; Higgins, John M.; Fathi, Amir T.; Hasserjian, Robert P.
Highlights AML patients with and without antecedent cytopenias were compared. AML patients with prior cytopenias were older and more likely to have dysplasia. Prior thrombocytopenia independently predicts prognosis in multivariable analysis.